Effectiveness of antiretroviral treatment in patients from pereira and manizales (2011)
Objective Evaluating the effectiveness of antiretroviral therapy in a sample of Colombian patients diagnosed as having HIV/AIDS and being treated by the Colombian Health Social Security System (CHSSS) Methods A descriptive study was conducted among 134 HIV/AIDS patients of any age or gender who had received antiretroviral therapy in the cities of Pereira and Manizales between July 1st 2008 and June 30th 2009. The following factors were assessed from the clinical history of the patients seen in three health insurance companies: viral load, CD4 count, antiretroviral treatment regimens, prescribed daily doses of medications, length of disease evolution, duration of therapy, history of opportunistic diseases, and drug costs. Results There was male predominance (91 men cf 43 women), mean age beingf 39 years, and an average of 59 months since diagnosis. All treatment regimens were defined by each drug's defined daily dose (DDD). The therapy was effective in 74.5 % of patients. Effectiveness was defined as being viral load and lt; 400 copies/ml. About 79.1 % of patients had had their viral load measured during the last 6 months. Non-adherence to treatment and a history of having acquired 2 other sexually- transmitted infections were associated with an increased risk of uncontrolled HIV infection. The average value of drugs per year per patient was $4,077.2 ± 3,043.8 U.S. dollars/year. Conclusions Non-adherence to treatment remains one of the most important issues regarding antiretroviral therapy effectiveness, so programmes intended to control HIV/ AIDS must address this problem.